Analysis Of The Effect Of Blasting Pattrerns On Ground And Building Vibration Levels Around The Mine At Blasting In Pit 2 Banko West PT Bukit Asam Tbk tanjung Enim, South sumatera Province - Indra Hot Daniel Hutasoit; Irvani Irvani; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2020)
PT Bukit AsamTbk is one of the coal mining companies in Indonesia that uses an open pit mining system. Demolition of B2-C overburden rocks at the location of electrification mining in Pit 2 Banko Barat is not economical if it is doing by ripping-dozing process so that drilling and blasting activities are carried out. After blasting activities, ground vibration will arise as an effect of the blasting. It is known that the distance of the blasting location with the residential area is at a distance of 1350-1800 m for this reason that vibration measurements must be carried out with the Blasmatet III device. Ground vibration is one of the problems that must be minimized so that the ground vibration level is in accordance with SNI 7571; 2010 did not exceed the vibration threshold that could cause damages, especially for residents. The ground vibration level can be controlled in various ways such as setting the point initiation point, setting the delay time with a higher value, planning the powder factor and finally using the Air deck method. Based on research carried out for 60 days with blasting 17 times which produces different vibrations. The vibration value used for the comparison of the effects of the blasting pattern is used in 6 data, 3 data for the Box cut blasting pattern, which are 0.52, 0.53, 0.56 and for data on the Corner cut blasting pattern which is 0.63, 0.69, 0.73. While for the comparison of data using Air deck, 6 data are used, 3 values of the results of the vibration of the water deck method are 0.73, 0.69,58 and for non-Air decks the results of the vibration are 1.17, 1.05, 0, 88. Calculation of the results of the comparison of the vibration comparison using the delay time there are 6 data used, namely 3 with a delay time of 42 & 67 with the results of vibration, namely, 0.58, 0.69, 0.73 while the delay time 42 & 109 the result of vibration is 0.50, 0.56, 0.58. Of the overall soil vibration values, settlements around the blasting area are in the safe category (PVS <3 mm / s).